2008
DOI: 10.1068/p5497
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Curvature on Haptic Judgments of Extent in Sighted and Blind People

Abstract: A series of experiments was carried out to examine the effect of curvature on haptic judgments of extent in sighted and blind individuals. Experiment 1 showed that diameters connecting the endpoints of semicircular lines were underestimated with respect to straight lines, but failed to show an effect of visual experience on length judgments. In experiment 2 we tested arc lengths. The effects of curvature on perceived path length were weaker, but were still present in this experiment. Visual experience had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…All of the coauthors (JRC, JFN, & AK) were able to experience this illusion on at least some sample trials during active haptic exploration. Given this, it was very interesting for us to find that similar subjective experiences have apparently occurred in other studies 32 . The participants of Heller et al 32 felt circular arcs as raised-line drawings; when asked to draw what they felt, some participants drew sinusoidally-shaped contours (see Fig.…”
Section: Discussionsupporting
confidence: 62%
“…All of the coauthors (JRC, JFN, & AK) were able to experience this illusion on at least some sample trials during active haptic exploration. Given this, it was very interesting for us to find that similar subjective experiences have apparently occurred in other studies 32 . The participants of Heller et al 32 felt circular arcs as raised-line drawings; when asked to draw what they felt, some participants drew sinusoidally-shaped contours (see Fig.…”
Section: Discussionsupporting
confidence: 62%
“…The St. Louis Arch is the same height and width at the base, yet it looks much taller than it is wide. Heller et al (2008) reported similar perceptual overestimation of verticals in haptic size estimates of raised line curves and L patterns, and the illusion was found with solid wooden inverted-T and L shapes (Heller et al, 2003).…”
Section: Stephanie Kibble K K Brett Litwiller and Cassie Ambuehlmentioning
confidence: 50%
“…However, this result was not obtained when the subjects traced the stimuli 9 or in the unlimited traces group. Nonetheless, Heller et al (2008) found dif-f f ferences in path completion as a function of the number of traces, with smaller diameter judgments for nine traces or unlimited numbers of traces. Thus, path completion length was affected substantially by tracing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies have indicated the opposite: that early visual exposure in sighted individuals enhances performance on haptic tasks, while blind individuals show impaired performance -especially in tasks that relied on a spatial component (Bailes and Lambert 1986;Pasqualotto and Newell 2007;Postma et al 2008;Gori et al 2010). Yet other studies found no evidence for differences in haptic perception performance between blind and sighted participants (Heller 1989b;Morrongiello et al 1994;Gentaz and Hatwell 1998;Grant et al 2000;Postma et al 2007;Heller et al 2008;Alary et al 2009;Picard et al 2010;Norman and Bartholomew 2011;Baumgartner et al 2015;Bonino et al 2015). Neuroimaging studies of haptic perception mainly found overlapping neural recruitment between congenitally blind and sighted participants, with the exception of the visual areas, which were more (extensively) activated in congenitally blind participants (Rosler et al 1993;Roder et al 1997;Ricciardi et al 2007;Amedi et al 2010;Bauer et al 2015).…”
Section: Introductionmentioning
confidence: 92%